A union representative's perspective of declining union membership - Melvin J. Rivers; Tim Truitt (International Journal of Management, Economics and Social Sciences (IJMESS), 2014)
Union membership has declined 24.2 percent since 1945. Declining union membership leads to economic losses for labor unions. The problem is relevant to scholars and the labor movement, requiring a deeper understanding of union membership decline. In this qualitative study, experiences with declining union membership are explored with union representatives in Los Angeles County. The conceptual framework uses three models: the utility of union membership, human motivation, and collective bargaining to identify relevant elements of union membership decisions. Twenty face-to-face interviews were conducted with participants who had a minimum of 3 years experience as a full-time union representative. The data were coded, and themes developed using the modified van Kaam method and NVivo 10 software. Three primary emergent themes resulted: (a) globalism is the primarily perceived cause of declining union membership, (b) unions should be more effective in collective bargaining, and (c) communication with union members must increase. The results from this study could be used to improve internal union communication, increase operational efficiency, and develop leadership training. The implications for positive social change include new insights to support labor union leaders in efforts to identify relevant needs, increase membership, retain jobs, and improve the economic health of their members.
Keywords: J08; J51; J52; M54; 330; Unions; Collective Bargaining; Union Membership; Union Study; Union Decline; Trade Unions